Precision Nutrition: Using Nutrigenetic Concepts In Personalized Nutrition - Mohd Nazri Abdul Rahman; Nor Hayati Muhammad (Fakulti Pengajian Islam, Universiti Malaysia Sabah, 2023)
This article discusses the significance of nutrition, genetics, and precision approaches in improving public health and personalized care. Precision Nutrition is an individualized dietary approach that takes into account a person's genetic, environmental, and lifestyle factors, offering more personalized recommendations compared to traditional nutrition science, which focuses on average responses. Nutrigenomics, comprising nutrigenomics and nutrigenetics, explores how genetics and diet interact to influence various diseases. While monogenic diseases can sometimes be managed through dietary adjustments, common conditions like heart disease, diabetes, obesity, and cancer result from complex interactions between genes, environment, and diet. Nutrigenomics provides insights into disease prevention and personalized nutrition. Nutrigenetics focuses on how an individual's genetic makeup affects their responses to diet, impacting health, well-being, and disease susceptibility. This knowledge helps prevent or manage diet-related diseases and offers personalized dietary guidance. In complex diseases like type 2 diabetes (T2DM), genetics play a significant role, but identifying causative genes is challenging due to multiple genes and environmental factors. Obesity is influenced by genetic and environmental factors, with over 600 gene markers associated with human obesity. Recent technologies can analyze genetic variations involved. Precision nutrition, encompassing various omics technologies, tailors’ dietary guidance to individual factors, providing personalized advice for better health outcomes. Challenges include the need for well-designed clinical trials, cost-effective technology, healthcare provider education, ethical considerations, and accessibility. Precision nutrition has the potential to revolutionize nutrition science, offering tailored dietary recommendations based on individual differences in gene expression and enhancing overall health through the collaboration of multiple fields.